Тяжесть, невесомость, перегрузка - Левантовский Владимир Исаакович (Народный университет, 1964)
Экземпляры: СЭ (20220506) / Инвентарный номер: 0143123 / Сис.шифр: 531 / Авт.знак: Л 34 / ГРНТИ: 29 / ББК: 22